Impacts of extensive driftnet fishery and late 1990s climate regime shift on dominant epipelagic nekton in the Transition Region and Subtropical Frontal Zone: Implications for fishery management. (January 2017) - Ichii, T.; Nishikawa, H.; Igarashi, H.; Okamura, H.; Mahapatra, K.; Sakai, M.; Wakabayashi, T.; Inagake, D.; Okada, Y.
Highlights: We assessed the impacts of the driftnet fishery on flying squid, pomfret and blue shark. These three stocks were assessed to be at MSY, overfished and underfished, respectively. We assessed impacts of the late 1990s regime shift on flying squid, saury and pomfret. Squid and saury appear to be more susceptible to the regime shift than pomfret. Abstract: We investigated the impacts of extensive anthropogenic (high seas driftnet squid fishery) and natural (late 1990s major climate regime shift) events on dominant epipelagic fish, squid, and shark in the central North Pacific Transition Region based on a driftnet survey covering the years 1979–2006. Fishing was conducted by Japan, Korea and Taiwan to target neon flying squid in the period 1979–1992, resulting in a decline in stocks of the target species and non-target species (Pacific pomfret and juvenile blue shark), which were by-catch of this fishery. The catch was found to be at the maximum sustainable yield (MSY) level for neon flying squid, the underfished level for juvenile blue shark, but the overfished level for Pacific pomfret. The MSY of Pacific pomfret indicated that this species is more susceptible to exploitation than previously considered. In response to the late 1990s regime shift, neon flying squid and Pacific saury showed low stock levels in 1999–2002 and 1998–2002, respectively, as a result of reduced productivity in their nursery grounds (the Subtropical Frontal Zone and Kuroshio Extension Bifurcation Region, respectively). On the other hand, Pacific pomfret showed no decreasing trend in stock during the low- and intermediate-productivity regimes because of the high productivity of their main spawning/nursery ground (Transition Zone Chlorophyll Front), which was independent of the regime shifts. Thus, squid and saury appear to be more susceptible to the regime shift than pomfret. We discuss the implications for stock management of the species-specific responses to the fishery and the regime shift.